PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI NILAI-NILAI PANCASILA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK KELAS V SD NEGERI MAYANGAN 4 - Nur Faradilah, Azmi; Arya Wardana, Ludfi; Prastiwi Sriwijayanti, Ribut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problem Based Learning (PBL)-based Student Worksheets (LKPD) represent an innovative teaching material Designed to address the low creative thinking skills among elementary school students in Pancasila Education learning. This research is motivated by classroom conditions at SDN Mayangan 4 which remain dominated by lecture methods and conventional worksheets, resulting in students' inability to optimally develop creative thinking indicators including fluency, flexibility, originality, and elaboration. The research aims to produce PBL-based worksheets that are valid, practical, and effective in improving creative thinking skills of fifth-grade students. Using a Research and Development (R&D) method with the ADDIE model Analysis, Design, Development, Implementation, and Evaluation data were collected through interviews, observations, expert validation sheets, student response questionnaires, and pretest-posttest assessments. Results demonstrate that the PBL-based LKPD received media expert validation of 93.75% and material expert validation of 91.6%, both categorized as highly valid. Student response reached 98.75% in the highly practical category. N-Gain Analysis yielded an average of 0.65, classified as medium, indicating effective improvement in students' creative thinking skills. These findings reinforce the argument that integrating PBL syntax into worksheets effectively stimulates student creativity while deepening contextual understanding of Pancasila values.